Formation of the natural and ecological framework of land use at the regional level in the context of ensuring environmental stability: methodological and methodical approaches - TRETIAK, Anton; TRETIAK, Valentyna; KAPINOS, Nataliia; STRELNYK, Viktoriia; PETROVA, Nataliia (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. Assessment of the ratio within administrative entities of different categories of land or types of land use in the context of environmental value according to the criterion of resource-consuming (resource-exploiting), environmental and reserve land use allows developing recommendations for the transformation of the land use structure to transfer lands to the category of protected elements and buffer zones of the natural and ecological framework of the land use system. Methods. The ecological stability methodology was applied, which makes it possible to assess the prospects for the formation of a single natural and ecological framework of the Sumy region of Ukraine. Results. Based on the results of the assessment, the prerequisites for the formation of the natural and ecological framework of the land use system in the Sumy region of Ukraine according to the criterion of resource-consuming (resource-exploiting), environmental and reserve land use of environmental value can be determined as favorable. A serious limiting factor in the formation of the ecological framework is the inclusion of the ecological network of agricultural lands in the land use system. In this regard, the creation of a natural and ecological framework for the land use system of the Sumy region of Ukraine and other regions now depends to a greater extent on the development and improvement of legal mechanisms. Conclusions. The concepts of "ecological framework", "element of ecological framework", "functional use of land", "transformation of functional use of land" should be enshrined in land and environmental legislation, which will allow determining the appropriate land use regimes, as well as reducing the anthropogenic impact on the territory individually for each element of the framework. An increase in the share of lands that perform environment-forming functions should be accompanied by diversification and intensification of land use in territories outside the natural and ecological framework.
Keywords: natural and ecological framework; land use; ecological network; ecological stability